C–H activation reactions of nitroarenes: current status and outlook. Issue 39 (23rd September 2021) - Sengupta, Saumitra; Das, Parthasarathi
Abstract : The current landscape of nitro group directed C–H activation reactions of (hetero)arenes is reviewed. Abstract : Ring substitution reactions of nitroarenes remain an under-developed area of organic synthesis, confined to the narrow domains of SN Ar and SN ArH reactions. While searching for alternative methodologies, we took stock of the C–H activation reactions of nitroarenes which unearthed a variety of examples of nitro directed regioselective C–H functionalization reactions such as ortho -arylation, -benzylation/alkylation, and -allylation, oxidative Heck and C–H arylation reactions on (hetero)aromatic rings. A collective account of these reactions is presented in this review to showcase the existing landscape of C–H activation reactions of nitroarenes, to create interest in this field for further development and propagate this strategy as a superior alternative for ring substitution reactions of nitroarenes. The prospect of merging the C–H activation of nitroarenes with C–NO2 activation, thereby harnessing NO2 as a transformable multitasking directing group, is also illustrated.